Price-quality ratios in value-for-money awards. Issue 3 (1st March 2015) - Kiiver, Philipp; Kodym, Jakub
Abstract : This article presents a simple and objective formula to determine a tender's price-quality ratio, for the purpose of value-for-money awards, which is literally quality divided by price (Q/P). Most formulas used in public procurement today first translate prices into points, in a process which has several flaws, and in the end they do not produce any actual ratios, a fact which makes them less objective. To adjust the proposed Q/P formula to the relative weight of the price criterion from the buyer's point of view, all tenders start out with a fixed quality score to compress or expand quality differences between them. Tenders then compete for the remaining range of quality points up to the maximum, and in the end have their quality score divided by the price that they offer.